Microcurricular innovation for the construction of assessment instruments for pedagody students (Revista Electrónica Calidad en la Educación Superior, 2022)
This applied and participative investigation considers a sample of 60 students of a total 180, distributed over careers of Special Education, Pre-school Education. Diagnostics reveal difficulties in analysis and reflection skills of students based in the building of evaluation instruments. Considering this, an innovative micro-curriculum plan is developeded including the problem identification, building, executing and evaluation of the procedure.
Keywords: Micro-curriculum innovation; initial instructor formation; evaluation